A Novel Fluorescent Test Papers Based on Carbon Dots for Selective and Sensitive Detection of Cr (VI) - Yang, Yizhou; Chen, Xuemei; Wang, Yangyang; Wu, Miao; Ma, Yinan; Yang, Xudong (Frontiers in Chemistry, 2020)
In recent years, carbon dots (CDs) are promising fluorescence probes for ions detection. In this paper, the CDs (with an average diameter of 5.5 nm) were synthesized through a simple one-step hydrothermal carbonization of eathylene diamine tetraacetic acid (EDTA) salt. The CDs have strong yellow photoluminescence (PL) with a maximum emission intensity at 550 nm under an excitation wavelength of 450 nm. As the electron transfer will occur between Cr (VI) and the CDs, yellow fluorescence was quenched after the addition of Cr (VI) ions. The CDs probe allows the detection of Cr (VI) ions over a concentration range from 0 to 0.1 M (R2 = 0.987) and the lower detection limit is 10-5 M. Simultaneously, the CDs show highly selectivity and stability towards the detection of Cr (VI) ions.